Efeito da estrutura de hábitat, da vegetação e da perturbação humana sobre a avifauna: variações metodológicas, espaciais e temporais em áreas verdes urbanas - Marques, Renata Leal (2017)
Urbanization is growing around the world, causing rapid changes in landscapes and urban green areas, and its importance is increasing for both human being and urban ecology. Several environmental factors influence the urban avifauna, being essential to plan and manage the urban green spaces for the conservation of this animal group. This work evaluated the effect of habitat quality and human disturbance on avifauna, regarding methodological, spatial and temporal variations in 40 urban green areas (public squares) of Uberlândia, MG, Brazil. Initially, we evaluated two methods of bird sampling, the point method and the zig-zag method, in order to test its application in urban areas. Next, we evaluated the responses of the avifauna to the structure of the habitat and the human disturbance, in a spatial and temporal way. Finally, we verified the relation of the urban avifauna with the vegetation present in the green areas investigated. We verified that the zig-zag method allowed a greater number of bird species and individuals to be recorded, as well as a greater number of behaviors, which demonstrates their effectiveness in the urban environment and importance in the analysis of the ave-habitat relationship. Few studies use the zig-zag method, which is why we encourage its use in the urban area, adapting it with the addition of acoustic logging in order to make it even more efficient and less laborious. The community of birds in squares of Uberlândia did not show significant changes, in the course of five years, in terms of the richness, abundance and composition of species. This can be explained by the fact that changes in the urban environment over the study period may not have been reflected in the bird community due to the relatively short time between evaluations. However, it is important to note that, despite the fact that there were no changes in the composition of the avifauna in the areas surveyed, there was a clear tendency to reduce groups more sensitive to the effects of urbanization. Therefore, it is important to continue the monitoring of birdlife in the city of Uberlândia, in order to confirm or not this trend. It is necessary to maintain urban green areas and improve the quality of these environments, in order to guarantee the presence of an even more diversified birdlife than the one currently found in the city of Uberlândia. Besides that, we verified that the richness of species of native and exotic plants were similar, while the abundance of exotic plants was higher. This is significant since there is a preference of the urban avifauna to forage, reproduce and rest on native plant species. In addition, we also verified that the different types of interactions between the avifauna and the vegetation present in the urban environment differed, and it is important to incorporate the different networks of interactions involved in the bird-plant relationship, in order to promote the conservation of biodiversity in this type of environment.